Compressible modes in a square lid-driven cavity - Bergamo, Leandro Fernandes; Gennaro, Elmer Mateus; Theofilis, Vassilis; Medeiros, Marcello Augusto Faraco (Elsevier B.V., 2015)
This paper studies the effect of compressibility on the linear stability of a two-dimensional lid-driven cavity flow in the subsonic regime. The base flow is generated by high fidelity direct numerical simulation and a biglobal mode instability analysis is carried out by a matrix forming approach. The eigenvalue problem is discretized by high-order finite differences and Arnoldi algorithm is used to reduce the size of the problem. The solution procedure uses sparse matrix techniques. Influence of Mach number on the modes known from incompressible calculations is presented, showing that compressibility has a stabilizing effect. New modes that appear only for compressible flows are presented and their relationship with duct acoustics is investigated.
Keywords: Compressible flow; Global linear stability analysis; Compressible global linear instability; Cavity flow